Detrital zircon and igneous protolith ages of high-grade metamorphic rocks in the Highland and Wanni Complexes, Sri Lanka: Their geochronological correlation with southern India and East Antarctica - Kitano, I.; Osanai, Y.; Nakano, N.; Adachi, T.; Fitzsimons, Ian (Pergamon-Elsevier Science Ltd, 2018)
The high-grade metamorphic rocks of Sri Lanka place valuable constraints on the assembly of central parts of the Gondwana supercontinent. They are subdivided into the Wanni Complex (WC), Highland Complex (HC) and Vijayan Complex (VC), but their correlation with neighbouring Gondwana terranes is hindered by a poor understanding of the contact between the HC and WC. Laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) U–Pb dating of remnant zircon cores from 45 high-grade metamorphic rocks in Sri Lanka reveals two domains with different age characteristics that correlate with the HC and WC and which help constrain the location of the boundary between them. The HC is dominated by detrital zircon ages of ca. 3500–1500 Ma from garnet–biotite gneiss, garnet–cordierite–biotite gneiss, some samples of garnet–orthopyroxene–biotite gneiss and siliceous gneiss (interpreted as paragneisses) and igneous protolith ages of ca. 2000–1800 Ma from garnet–hornblende–biotite gneiss, other samples of garnet–orthopyroxene–biotite gneiss, garnet–two-pyroxene granulite, two-pyroxene granulite and charnockite (interpreted as orthogneisses). In contrast, the WC is dominated by detrital zircon ages of ca. 1100–700 Ma from paragneisses and igneous protolith ages of ca. 1100–800 Ma from orthogneisses. This clearly suggests the HC and WC have different origins, but some of our results and previous data indicate their spatial distribution does not correspond exactly to the unit boundary proposed in earlier studies using Nd model ages. Detrital zircon and igneous protolith ages in the HC suggest that sedimentary protoliths were eroded from local 2000–1800 Ma igneous rocks and an older Paleoproterozoic to Archean craton. In contrast, the WC sedimentary protoliths were mainly eroded from local late Mesoproterozoic to Neoproterozoic igneous rocks with very minor components from an older 2500–1500 Ma craton, and in the case of the WC precursor sediments there was possibly additional detritus derived from early to middle Neoproterozoic metamorphic rocks. The relic zircon core ages in the HC are comparable with those of the Trivandrum Block and Nagercoil Block of southern India. In contrast, those ages in the WC match the Achankovil Shear Zone and Southern Madurai Block of southern India. These comparisons are also supported by Th/U ratios of detrital zircon cores from paragneisses (Th/U ratios of >0.10 for the former and not only >0.10 but also ≤0.10 for the latter). Comparisons with the Lützow-Holm Complex of East Antarctica indicate that the geochronological characteristics of the HC and WC broadly match those of the Skallen Group, and the Ongul and Okuiwa Groups, respectively.